2012
DOI: 10.1002/ptr.4860
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator Activity of Aerial Parts of Polygonatum verticillatum Augmented by Anti‐inflammatory Activity: Attenuation of Ca2+ Channels and Lipoxygenase

Abstract: Polygonatum verticillatum is commonly used for the treatment of asthma and inflammation. The current study was aimed to scrutinize the pharmacological profile of methanolic extract of the aerial parts (PA). Isolated tracheal preparations were used for the evaluation of bronchodilatory activity, whilst the in vivo carrageenan-induced paw oedema test and an in vitro lipoxygenase (LOX) inhibitory assay were used for the assessment of the anti-inflammatory profile of PA. When tested against carbachol and K⁺ (80 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This test has been commonly used as an experimental animal model for acute inflammation mainly mediated by histamine, serotonin, bradykinin and increased synthesis of prostaglandins in the damaged tissue (initial phase) which is subsequently sustained by the release of prostaglandins and nitric oxide and by the involvement of polymorphonuclear cells (second phase) (Di Rosa and Willoughby, 1971;Gupta et al, 2008). The theory that best explains anti-inflammatory and antinociceptive activities of NSAIDs in these experimental models is in part based on the discovery that these drugs inhibit prostaglandin biosynthesis (Khan et al, 2013a(Khan et al, , 2013bMuhammad et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…This test has been commonly used as an experimental animal model for acute inflammation mainly mediated by histamine, serotonin, bradykinin and increased synthesis of prostaglandins in the damaged tissue (initial phase) which is subsequently sustained by the release of prostaglandins and nitric oxide and by the involvement of polymorphonuclear cells (second phase) (Di Rosa and Willoughby, 1971;Gupta et al, 2008). The theory that best explains anti-inflammatory and antinociceptive activities of NSAIDs in these experimental models is in part based on the discovery that these drugs inhibit prostaglandin biosynthesis (Khan et al, 2013a(Khan et al, , 2013bMuhammad et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported to possess Ca ++ antagonist activity, which might be responsible for the bronchodilatory action (Ghayur and Gilani, 2006b;Ghayur et al, 2008), although additional mechanism(s) cannot be ruled out. Sarcococca saligna, Borago officinalis, Achillea millefolium, olives (Olea europea), cardamom (Elettaraia cardamomum), Swertia chirata, Desmostachya bipinnata, Tephrosia purpurea and Polygonatum verticillatum were also found to exhibit CCB effect, which may account for their bronchodilatory potential (Ghayur and Gilani, 2006a;Gilani et al, 2007, Khan and Gilani, 2011a, 2011bKhan et al, 2011;Khan et al, 2012d;Abdur Rahman et al, 2013;Janbaz et al, 2013;Khan et al, 2013aKhan et al, , 2013b, and it would not be surprising to see co-existence of other pharmacological mechanisms in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical study: Asthmatic patients Improved expiratory flow volume Fu, 1989 Polygonatum verticillatum (L.) All. In vitro study: Carbachol and K + precontracted guinea pig-isolated trachea Bronchodilation Khan et al, 2013aKhan et al, , 2013b Portulaca oleracea L. Clinical study: Measurement of forced expiratory volume, peak expiratory flow, maximal mid-expiratory flow and specific airway conductance in asthmatic patients…”
Section: Meliaceaementioning
confidence: 99%
“…Earlier studies on the medicinal potential of the plant has been reported to possess analgesic antimalarial and antioxidant (Khan et al, 2012d), metal accumulation (Khan et al, 2012f;Saeed et al, 2010a), phytotoxicity , antipyretic (Khan et al, 2013a), bronchodilatory and anti-inflammatory (Khan et al, 2012c), antibacterial (Khan et al, 2012e), and enzyme inhibition (Khan et al, 2013c) activities. Phytochemically, long-chain esters with potent tyrosinase inhibition has been reported (Khan et al, 2013b).…”
Section: Introductionmentioning
confidence: 96%